2016
DOI: 10.1080/19336896.2016.1163457
|View full text |Cite
|
Sign up to set email alerts
|

The nucleo-junctional interplay of the cellular prion protein: A new partner in cancer-related signaling pathways?

Abstract: ABSTRACT. The cellular prion protein PrP c plays important roles in proliferation, cell death and survival, differentiation and adhesion. The participation of PrP c in tumor growth and metastasis was pointed out, but the underlying mechanisms were not deciphered completely. In the constantly renewing intestinal epithelium, our group demonstrated a dual localization of PrP c , which is targeted to cell-cell junctions in interaction with Src kinase and desmosomal proteins in differentiated enterocytes, but is pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…c-Myc, cyclin D1, MMP7; [ 133 ]). The inhibition of β-catenin-TCF-4 transcriptional activity by plakoglobin was also demonstrated in a recent study that reported the interaction of both catenins with the cellular prion protein PrP(c) [ 83 , 134 , 135 ]. PrP(c) was shown to interact with actin, spectrin, annexin A2, plakoglobin, desmoglein 2, desmoplakin and c-Src in epithelial cells.…”
Section: Plakoglobin Tumor and Metastasis Suppressor Activitymentioning
confidence: 74%
See 1 more Smart Citation
“…c-Myc, cyclin D1, MMP7; [ 133 ]). The inhibition of β-catenin-TCF-4 transcriptional activity by plakoglobin was also demonstrated in a recent study that reported the interaction of both catenins with the cellular prion protein PrP(c) [ 83 , 134 , 135 ]. PrP(c) was shown to interact with actin, spectrin, annexin A2, plakoglobin, desmoglein 2, desmoplakin and c-Src in epithelial cells.…”
Section: Plakoglobin Tumor and Metastasis Suppressor Activitymentioning
confidence: 74%
“…PrP(c) interacted not only with plakoglobin but also with β-catenin and TCF-4 in both the cytoplasm and nucleus. Futhermore, the interaction of PrP(c) with β-catenin-TCF-4 stimulated its transactivation, whereas PrP(c)-plakoglobin interactions decreased it [ 134 , 135 ].…”
Section: Plakoglobin Tumor and Metastasis Suppressor Activitymentioning
confidence: 99%
“…In addition to truncated forms, PrP C can localize in the nucleus of different cell types including neural cells, and it interacts with structural chromatin components, principally histone H3; the interaction of PrP C with histone H3 suggests that PrP is involved in transcriptional regulation in the nucleus . Nuclear PrP interacts with distinct proteins involved in cell proliferation and cell junction in several cell types, and PrP participates in the process of DNA repair after genotoxic stress …”
Section: Discussionmentioning
confidence: 99%
“…Because all of the all analyzed sheep were healthy, and previously reported pathogenic codons (such as codons 136, 141, 146, 154, and 171) were not located in the studied indels, the present study cannot provide results on the relationship between these indels and scrapie susceptibility. As well as being considered a pathogenic control, PRNP has also become an emerging target gene for cancer therapies, because PrPc participate in the processes of intercellular junctions, tumor growth, and metastasis [43][44]. Further cancer investigations revealed that PrPc contribute toward the self-renewal of embryonic, tissuespecific, and cancer stem cells [44], which provides a potential basis for researching the PRNP regulation of animal phenotypic traits.…”
Section: Discussionmentioning
confidence: 99%